Hybrid flexible approach for Six Sigma implementation in constructional SME - Paslawski, Jerzy (Journal of Civil Engineering and Management, 2013)
Possibility of Six Sigma implementation in small/medium enterprise (SME) in construction industry is the goal of this paper. Robust conception of Six Sigma is taken as one option of flexible approach used in construction industry for risk management. High level of risk on the operations management is very important feature in comparison between construction industry and other economy branches. This problem is connected with very restricted level of automation and robotics, influenced environment, etc. Hierarchical culture with fragmentation of activity and low cost preferences as typical approach in construction industry seems to be important reasons of problems in Six Sigma implementation process. Presented conception is based on hybrid approach for flexibility implementation: robustness (Six Sigma), adaptation, simplification (Japan flexibility school) and modification of organizational culture. All four elements were fitted together for achievement of synergy effect.